Treinamento de força de alta frequência não é mais eficaz do que o treinamento de força de baixa frequência para aumentar a massa muscular e força em homens bem treinados - GOMES, Gederson Kardec (2017)
Strength training (TF) results in muscle hypertrophy (determined by the accumulation of proteins from each overlap of protein synthesis rate that exceeds the rate of degradation after a TF session) and increased maximal muscle strength (related to neural adjustments and muscle hypertrophy). As the TF proceeds, muscle strength and mass gains stagnate. The frequency manipulation (number of days that a group is trained in the week) of TF has been suggested as an important strategy to break this stagnation by promoting increased muscle strength and hypertrophy in well-trained individuals. Therefore, the objective of the study was to investigate whether high frequency TF is superior to low frequency TF in skeletal muscle adaptations (increase of muscle strength and mass). Twenty-three subjects (age 26.2 ± 4.2, experience with TF 6.9 ± 3.1) were randomly assigned to two groups: low frequency TF (TFBF, n = 12) and high frequency TF (TFAF, n = 11). The TFBF group trained each muscle group once a week in a split body routine, while the TFAF group trained each muscle group five times a week in a total body routine. Both groups performed the same number of sets (5-10 sets) and exercises (1-2 exercises per muscle group) per week, in which the intensity used for them was 70-80% of a maximal repetition (1RM) with 8 to 12 repetitions, five times a week. Muscle strength (1RM in bench press and barbell back squat), total and regional muscle hypertrophy (dual energy X-ray absorptiometry) were assessed before and at the end of the study. The results showed that there were increases in strength (TFBF and TFAF: bench press 5.6 kg and 9.7 kg and barbell back squat 8.0 kg and 12.0 kg, respectively) and muscle mass (p = 0.007) (TFBF e TFAF: 0.5 kg e 0.8 kg, respectively) in both groups (P <0.001), without difference between them (bench press, P = 0.168; barbell back squat, P = 0.312 and muscle hypertrophy, P = 0.619). The present study suggests that high frequency strength training is no more effective than low frequency strength training to increase muscle mass and strength in well-trained men.